Di Nan Tangah Inspired by The Antaan Baka Tradition in Paninggahan Nagari Solok Regency West Sumatra - Sari, Dermita Kumala; Rovylendes, Adjuoktoza; Syahril; Osmond, Dony (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The dance work “Di Nan Tangah”  is a contemporary dramatic dance piece inspired by the Antaan baka tradition in Nagari Paninggahan, Solok Regency, West Sumatra. The creation of this dance piece aims to reflect the socio-cultural conflicts that arise from differing views between traditional values, religious understanding, and modern lifestyles. The creation process for “Di Nan Tangah“ utilizes the creative method according to Alma M. Hawkins, which includes data collection and field observation, exploration, improvisation, formation, and evaluation. The movement elements are derived from Minangkabau silat movements and daily activities, adapted in a contemporary way. This work is supported by the use of minimalist digital music, dramatic lighting, simple makeup and costume, and pandan mat props as symbols of the Antaan baka tradition.